Sustained reductions in time to antibiotic delivery in febrile immunocompromised children: results of a quality improvement collaborative. Issue 2 (4th September 2015) - Dandoy, Christopher E; Hariharan, Selena; Weiss, Brian; Demmel, Kathy; Timm, Nathan; Chiarenzelli, Janis; Dewald, Mary Katherine; Kennebeck, Stephanie; Langworthy, Shawna; Pomales, Jennifer; Rineair, Sylvia; Sandfoss, Erin; et al.
Abstract : Background: Timely delivery of antibiotics to febrile immunocompromised (F&I) paediatric patients in the emergency department (ED) and outpatient clinic reduces morbidity and mortality. Objective: The aim of this quality improvement initiative was to increase the percentage of F&I patients who received antibiotics within goal in the clinic and ED from 25% to 90%. Methods: Using the Model of Improvement, we performed Plan-Do-Study-Act cycles to design, test and implement high-reliability interventions to decrease time to antibiotics. Pre-arrival interventions were tested and implemented, followed by post-arrival interventions in the ED. Many processes were spread successfully to the outpatient clinic. The Chronic Care Model was used, in addition to active family engagement, to inform and improve processes. Results: The study period was from January 2010 to January 2015. Pre-arrival planning improved our F&I time to antibiotics in the ED from 137 to 88 min. This was sustained until October 2012, when further interventions including a pre-arrival huddle decreased the median time to <50 min. Implementation of the various processes to the clinic delivery system increased the mean percentage of patients receiving antibiotics within 60 min to >90%. In September 2014, we implemented a rapid response team to improve reliable venous access in the ED, which increased our mean percentage of patients receiving timely antibiotics to its highest rate (95%). Conclusions: This stepwise approach with pre-arrival planning using the Chronic Care Model, followed by standardisation of processes, created a sustainable improvement of timely antibiotic delivery in F&I patients.